Analysis of Leading Sectors Supporting Tourism Using Location Quotient and Shift-Share in East Nusa Tenggara (2018-2022) - Amelia, Yesi; Husaini, Muhammad; Putri, Resha Moniyana (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This study examines the leading sectors supporting tourism in East Nusa Tenggara (NTT) Province from 2018 to 2022, utilizing Location Quotient (LQ) and Shift-Share analyses. By analyzing the Gross Regional Domestic Product (GRDP) across 21 districts and 1 city, the research identifies the transportation, accommodation, and information and communication sectors as critical contributors to tourism. The LQ analysis reveals that nine regions have transportation as a base sector, while four regions each specialize in accommodation, restaurant, iinformation, and communication. Kupang City stands out with all three sectors as basic. The Shift-Share analysis further indicates that most regions experience growth in the transportation sector driven by national trends, though many still face competitive challenges. These findings highlight the importance of enhancing infrastructure and services in these key sectors to bolster tourism development in NTT. The study offers valuable insights for regional planning and policymaking aimed at leveraging tourism for economic growth.